2021
DOI: 10.1371/journal.pone.0252408
|View full text |Cite
|
Sign up to set email alerts
|

The temperature of emotions

Abstract: Emotions and temperature are closely related through embodied processes, and people seem to associate temperature concepts with emotions. While this relationship is often evidenced by everyday language (e.g., cold and warm feelings), what remains missing to date is a systematic study that holistically analyzes how and why people associate specific temperatures with emotions. The present research aimed to investigate the associations between temperature concepts and emotion adjectives on both explicit and impli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(15 citation statements)
references
References 104 publications
(142 reference statements)
2
13
0
Order By: Relevance
“…Not all cases achieved complete agreement with existing studies; in our opinion, this is expected and generally aligns with a variety of findings presented in this area of research (see Barbosa Escobar et al (2021) ). First, other studies have been carried out for other countries or regions with different climates, and as a result, we can expect different associations.…”
Section: Resultssupporting
confidence: 90%
“…Not all cases achieved complete agreement with existing studies; in our opinion, this is expected and generally aligns with a variety of findings presented in this area of research (see Barbosa Escobar et al (2021) ). First, other studies have been carried out for other countries or regions with different climates, and as a result, we can expect different associations.…”
Section: Resultssupporting
confidence: 90%
“…On the one hand, different temperatures can influence emotional states (Noelke et al, 2016), and on the other hand, individuals' emotions can affect their ambient temperature perception and thermal comfort (Wang & Liu, 2020). Relevant to the present study, people from different countries tend to associate different temperature concepts with different emotions consistently (Barbosa Escobar et al, 2021). The latter authors found that people associate lower temperatures with negatively valenced, low arousal emotions, comfortable ambient temperatures with positively valenced, low-to-medium arousal emotions, and higher temperatures with positively valenced, high-arousal emotions, respectively.…”
Section: Affective Mechanismsupporting
confidence: 58%
“…Due to the nature of the dimensions involved, as Barbosa Escobar et al (2021) suggested, associations between visual textures and temperature may lie somewhere in the broad spectrum of crossmodal associations, with semantic congruence on one end and crossmodal correspondence on the other (Parise, 2016). The former refers to pairs of stimuli that are tied to the same identity or meaning (Chen & Spence, 2010), whereas the latter refers to links between low-level features from sensory modalities (Parise & Spence, 2013;Spence, 2011).…”
Section: Semantic Congruence Mechanismmentioning
confidence: 99%
“…In the main study, prior to viewing one randomly selected stimulus, participants indicated their mood (Peterson and Sauber 1983) and ATLoc (Barbosa Escobar et al 2021), both measures embedded in a series of questions designed to help participants ease into the study. After taking the virtual tour, participants completed measures of telepresence (as in Study 1), perceived illumination (Tsushima et al 2020), ATOS (Krause et al 2020), warmth and competence (Halkias and Diamantopoulos, 2020), customer-company identification (Bagozzi and Dholakia, 2006), and a comprehensive set of outcome variables (purchase intentions, word-of-mouth communications, and willingness-to-pay; Zeithaml and Parasuraman, 1996).…”
Section: Methodsmentioning
confidence: 99%